Assessing and enhancing pediatric residents’ knowledge and skills in tracheostomy care through simulation-based training - Ghandourah, Hasan; Townsi, Nada; Abualjdyel, Meral; Khan, Muhammed A.; Seebran, Narvanie; Mowalled, Salma; El Jamal, Winifred Mary; Kashqari, Haifaa; Selati, Saif (Frontiers in Pediatrics, 2025)
Background and ObjectivesThe pediatric residency program in Saudi Arabia currently does not include tracheostomy care as a competency. Research has indicated that nonsurgical residents have limited knowledge of tracheostomy management. This study aimed to establish the need for pediatric residents to be trained in tracheostomy care and the effectiveness of having such a training program.MethodsThis cross-sectional and interventional study included all pediatric residents who completed a self-assessment questionnaire of confidence levels, an objective knowledge assessment, and a hands-on routine pediatric tracheostomy tube change assessment on a mannequin. A targeted tracheostomy workshop was tailored to pediatric residents using didactic presentations and hands-on simulation practice.ResultsForty-two residents participated in this study. The residents had limited experience with tracheostomy care, as they had not received formal training in this area nor practiced changing a tracheostomy tube independently. Thirty-one residents (73.81%) felt incompetent in assessing patients with a tracheostomy, and 39 (92.86%) lacked confidence in performing tracheostomy tube change care. The levels of confidence among the residents, knowledge regarding management of tracheostomy, and clinical expertise in tracheostomy tube change was significantly higher after the workshop than their scores measured prior to the workshop.ConclusionThis study illustrates that the healthcare professionals in pediatrics are not self-assured and knowledgeable in the field of tracheostomy care and, thereby, establishes the necessity of a specific tracheostomy educational program to enhance the self-assurance, knowledge, and competency in performing the practice.